The role of community capacity building (CCB) in promoting local development: Analyzing leadership in the Hyderabad cantonment community - Ghulam Muhammad Abro; Faraz Hussain Kalhoro; Ahmad Alshammari; Bilal Hassan; Ghulam Qadir Abro; Akbar Ali Khan (PLoS ONE, 2026)
With leadership positioned as a key tenet, this study investigates the function of Community Capacity Building (CCB) in fostering local development. It combines quantitative survey data from Hyderabad Cantonment, Pakistan, with qualitative interview data using a mixed-methods design. The results show notable deficiencies in women’s leadership participation, resource mobilization, and participatory governance. The study suggests specific tactics to improve leadership for sustainable and inclusive development. The study creates an empirically supported, situation-specific, yet broadly applicable model for grassroots development. Creating localized policy recommendations that address governance deficiencies and integrating leadership roles using both qualitative narratives and quantitative insights are two important contributions. For academics and decision-makers looking to promote participatory governance in urban and semi-urban settings, the results offer useful evidence. It is important to note that findings reflect community perceptions of leadership effectiveness rather than objective performance indicators, and therefore should be interpreted as perception-based evidence rather than causal measurement.